Effect of lncRNA KCNQ1OT1 on autophagy and drug resistance of hepatocellular carcinoma cells by targeting miR-338-3p - Zhong, Weiwei; Dai, Qianqian; Huang, Qionghui (Cellular and Molecular Biology, 2020)
The current experiment aimed to investigate the effects of lncRNA KCNQ1OT1 on the proliferation, autophagy and drug resistance of hepatocellular carcinoma cells, as well as the potential molecular mechanism. Hepatocellular carcinoma SK-HEP-1 cells and DDP resistant SK-HEP-1/DDP cells were treated with cisplatin (DDP) of different concentrations (1 nmol/L, 2 nmol/L, 4 nmol/L, 8 nmol/L, 16 nmol/L). The survival rate of SK-HEP-1 and SK-HEP-1/DDP cells was determined by the CCK8 method. QRT-PCR was used to detect the levels of lncRNA KCNQ1OT1 and miR-338-3p in normal hepatocyte HH01, hepatocellular cell SK-HEP-1 and hepatoma cisplatin-resistant cell SK-HEP-1/DDP. Western blot was carried out to detect the expression levels of autophagy-related protein Beclin1 and proliferation-related protein P21 in cells. A dual-luciferase reporter assay system was performed to validate the relationship between KCNQ1OT1 and miR-338-3p. After the treatment of 1 nmol/L, 2 nmol/L, 4nmol/L, 8nmol/L and 16nmol/L cisplatin (DDP), the survival rate of SK-HEP-1/DDP cells is higher than that of SK-HEP-1 cells. The level of lncRNA KCNQ1OT1 was increased successively in HH01, SK-HEP-1 and SK-HEP-1/DDP cells, while miR-338-3p was decreased successively. Silencing lncRNA KCNQ1OT1 or over-expressing miR-338-3p combined with 16nmol/L DDP treatment reduced the survival rate of SK-HEP-1/DDP cells and up-regulate levels of P21 and Beclin1 proteins. LncRNA KCNQ1OT1 targeted and negatively regulated the expression of miR-338-3p. Inhibition of miR-338-3p reversed the effect of silencing lncRNA KCNQ1OT1 on survival, autophagy and cisplatin sensitivity of SK-HEP-1/DDP cell. LncRNA KCNQ1OT1 targets miR-338-3p to regulate the survival rate and autophagy of SK-HEP-1/DDP cells and improve the cisplatin sensitivity of SK-HEP-1/DDP cells. LncRNA KCNQ1OT1 is a potential molecular target for hepatocellular carcinoma.